Population Density, Developmental Period and Fecundity of Anopheles Mosquito (Diptera: Culicidae) in the Gezira State, Sudan - Abdalla, Abdalla Ibrahim; E. M. Hassan, Ahmed; A. A. Kehail, Mutaman (Gezira Journal of Health Sciences; Vol 13 No 1 (2017), 2017)
In the Gezira State, insecticides were used for many years for controlling mosquitoes and other agricultural pests. The objective of this work was to study the population density, the developmental periods the reproductive periods and the fecundity of Anopheles mosquitoes in the Gezira State, Sudan. The study was conducted in three sites; Elmanagel, Elhosh and Wad Medani.Ten of one-day old or less of the cultured adult males and females of A. pharoensis wewe transferred separately to cage. The female pre-oviposition period, daily number of eggs deposited, the oviposition period, the post oviposition period, the adult longevity and the average number of eggs per female were recorded. The results revealed that, the number of A.arabiensis larvae collected from  the three sites was higher than that of A. pharoensis and A. funestus during the two seasons (2009 and 2010). The number of A. funestus adults collected at Wad Medani site during the two seasons was lowest than that collected from El Managel and El Hosh. The incubation period of the eggs, was relatively similar in all Anopheles species, as same as the larval period. The pupal period was relatively longer in A. funestus (2.4 days) and A. pharoensis (2.2 days) than in A.arabiensis (2 days). Adult A. pharoensis lived relatively longer (21 days) than A arabiensis and A. funestus (20 days). The total life cycle was relatively longer (32 days) in A. pharoensis than in A. arabiensis and A. funestus (30 days for each). Females of all species of Anopheles mosquito oviposited after one day from their emergence from the pupae and took also one day before they oviposit again. The oviposition period was significantly longer in A. arabiensis (3.3 days) than in A. pharoensis (2.5 days) and A. funestus (1.8 days). The oviposition rate was significantly higher in A. arabiensis (191) than in  A. pharoensis (150) and A. funestus (79). The fecundity of A. arabiensis (624 eggs/female) was significantly greater than that of A. pharoensis (391 eggs/female) and A. funestus (141 eggs/female). Such study should be run periodically for all sites in the Gezira State and neighboring States.